Exploring the Interplay of Political Markets and Political Utility - Kenaphoom, Sanya (วารสารการบริหารปกครอง มหาวิทยาลัยกาฬสินธุ์, 2024)
Political markets are the settings in which political parties vie with one another for support by offering votes and influence in exchange for policies and promises. The satisfaction or value that people and groups derive from political decisions and outcomes is measured by political utility. When combined, these ideas draw attention to the transactional character of politics, in which parties trade support in exchange for beneficial policy results. In the end, the political utility that these exchanges produce is a gauge of how well political decisions meet the interests and preferences of the various constituents. Thus, this paper aims to explore the Interplay of Political Markets and Political Utility. This paper is documentary research. The results found that the connection between political markets and political utility were; (1) Incentive Structure, (2) Resource Allocation, (3) Competition and Exchange, (4) Rational Decision-Making, (5) Dynamic Nature, (6) Subjective Evaluation, and (7) Feedback loop. It was concluded that several characteristics, including incentive structures, resource allocation, competition and exchange, rational decision-making, dynamic nature, subjective evaluation, and feedback loops, define the relationship between political markets and political utility. These components serve as examples of how political actors work within markets to maximize gains and efficiency in the pursuit of political objectives.